Use Of Quantitative Modelling To Elucidate The Roles Of The Liver, Gut, Kidney, And Muscle In Ammonia Homeostasis And How Lactulose And Rifaximin Alter This Homeostasis - Levitt MD; Levitt DG (International Journal of General Medicine, 2019)
Michael D Levitt,1 David G Levitt2 1Research Service, Veterans Affairs Medical Center, Minneapolis, MN 55417, USA; 2Department of Integrative Biology and Physiology, University of Minnesota, Minneapolis, MN 55455, USACorrespondence: David G LevittDepartment of Integrative Biology and Physiology, University of Minnesota, 6-125 Jackson Hall, 321 Church St. S. E., Minneapolis, MN 55455, USATel +1 612 594 0272Fax +1 612 301 1543Email levit001@umn.eduAbstract: Humans must eliminate approximately 1M of ammonia per day while maintaining the blood concentration of this potent neurotoxin at a concentration of only about 30 μM. The mechanisms producing such effective ammonia homeostasis are poorly understood by clinicians due to the multiple organs (liver, gut, kidney and muscle) involved in ammonia homeostasis. Based on literature values we present a novel, simplified description of normal and disordered ammonia and the potential mechanisms whereby the drugs used to treat hepatic encephalopathy, lactulose and rifaximin, lower the blood ammonia concentration. Concepts discussed include the following: 1) only about 44 mmol of ammonia/day (4.4% of total production) reaches the peripheral circulation due to the efficient linkage of amino deamination and the urea cycle in hepatic mitochondria; 2) the gut and kidney contribute roughly equally to delivery of this 44 mmol/day to systemic blood; 3) the bulk of gut ammonia production seemingly originates in the small bowel from bacterial deamination of urea by bacteria and mucosal deamination of circulating and ingested glutamine; 4) the apparent production of ammonia in the small bowel markedly exceeds that quantity that enters the portal blood, indicating that ammonia disposal mechanisms in the small bowel play a major role in ammonia homeostasis. With regard to the hyperammonemia of chronic liver disease: 1) shunting of portal blood around the liver, by itself, can account for commonly observed ammonia elevations; 2) severe portal hypertension causes an increased release of ammonia by the kidney; 3) high blood ammonia is associated with an unexplained massive increase in the muscle uptake of ammonia that could play an important role in limiting hyperammonemia; and 4) a major action of lactulose administration may be the enhancement of ammonia uptake by small bowel bacteria, while the mechanism of action of rifaximin is unclear.Keywords: encephalopathy, urease, glutamine, deamination, urea